Beyond the Sacred: Analyzing the Transformation of Surakarta’s Sekaten and Its Implications for Islamic Teaching and Learning - Fatimah Nur Sholikhah; Fadil Hidayatulloh Rohman; Fadhil Fath Alimi (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2025)
The annual Sekaten tradition in the Kasunanan Surakarta Palace illustrates how traditional religious practices continue to adapt to modern life. Originally intended to spread Islam and preserve Javanese culture, Sekaten has shifted toward a blend of entertainment, tourism, and digital engagement. While previous research has mostly examined its historical, sociological, and ritual aspects, there is still limited study on how Sekaten functions as a non-formal educational space, especially for young people. This study addresses that gap by exploring how the younger generation interprets the changing meaning of Sekaten. Using qualitative methods historical and phenomenological approaches supported by document analysis, observation, and interviews with youth and palace officials the research finds that Sekaten is increasingly viewed through recreational and commercial lenses. As a result, its religious value is gradually declining. Today, young people tend to see Sekaten mainly as a site of entertainment and digital cultural expression. The study concludes that these shifts reflect broader social and cultural transformations. It recommends a balanced preservation strategy that maintains traditional sacred elements while adapting to the needs of modern youth in education.